2011
DOI: 10.5251/ajfn.2011.1.4.171.177
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and bioactive contents of some selected Vegetables in Nigeria: Processing and Varietal effects

Abstract: Leaves of four varieties of vegetable were subjected to two processing methods which are sun drying and blanching. This study aims at assessing the effect of some post harvest treatments on the nutrient, anti-nutrient and anti-oxidant potentials of the leafy vegetables. In this study fresh leaves of Vernonia amygdalina, Basella alba, Telferia accidentalis and Talinium Triangulare were subjected to the processing methods mentioned earlier, the vegetables were blanched at 60 o C. The proximate, bio-active compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…Lower value of 1075 μg of β-carotene/100 g in bathua leaves has been reported in IFCT [7] while some other authors [21,27,34] have reported higher β-carotene content (9300 µg/100 g; 26380 μg/100 g and 114610 µg/100 g respectively) in bathua leaves as compared to the present study. Results of β-carotene in mint leaves (Menthaspicata) are in agreement with other previously published data [10,11].…”
Section: Tubers and Other Vegetablescontrasting
confidence: 51%
“…Lower value of 1075 μg of β-carotene/100 g in bathua leaves has been reported in IFCT [7] while some other authors [21,27,34] have reported higher β-carotene content (9300 µg/100 g; 26380 μg/100 g and 114610 µg/100 g respectively) in bathua leaves as compared to the present study. Results of β-carotene in mint leaves (Menthaspicata) are in agreement with other previously published data [10,11].…”
Section: Tubers and Other Vegetablescontrasting
confidence: 51%
“…Fèfèbrou had the highest value (0.309 ± 0.002 mg / 100 g). In Nigeria, Adegunwa et al, (2011) reported β carotene levels in fresh leaves ranging from 0.240 to 0.264 mg / 100 g. According Sluijs et al, (2015), diets high in β-carotene were shown to be associated with a reduced occurrence of type 2 diabetes. Adequate intake of these leafy vegetables could therefore be advantageous.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Just like many other green leafy vegetables, pumpkin leaf is tasty and nutritious and is popular in countries such as Kenya, Malawi, Zambia, Zimbabwe, among others. The leaves are a valuable source of nutrients (which are usually in short supply in daily diets) especially in rural areas (Lymo et al, 1991;Mepba et al, 2007) where they contribute substantially to minerals, fiber, protein and vitamins, especially β-carotene and ascorbic acid (FAO,1988;Mwaniki et al, 1999;Adegunwa et al, 2011;Kakade and Neeha, 2014). Pharmacologically, leaves in the family of Cucurbitaceae are believed to have a number of health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Although this kind of processing has been regarded as significant in preserving pumpkin leaves, the steps of blanching and sun-dehydration have great potential of reducing some nutrients in the vegetable, more especially, ascorbic acid (vitamin C), which is soluble in water and prone to oxidation upon exposure to light (Lawal et al, 2015;Okpalamma et al, 2013;Adegunwa et al, 2011). Despite the fact that, there is a possibility that the blanching and dehydration can lead to ascorbic acid loss, there is no clear information on the amount that is lost as a result of this processing method.…”
Section: Introductionmentioning
confidence: 99%